2012
DOI: 10.1136/injuryprev-2012-040590e.5
|View full text |Cite
|
Sign up to set email alerts
|

Fractures following falls in Sri Lanka

Abstract: Background Trauma is a leading cause of hospital admissions in Sri Lanka and of which, a major component are fractures sustained due to falls. However, only limited information is available on this important public health problem. Aim To describe the demography and characteristics of fractures sustained following falls, in Sri Lanka. Methods A descriptive, cross-sectional study was conducted on patients who sustained fractures following falls. The sample included all patients who attended the Orthopaedic post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study had revealed that 35.8% of patients with fractures following injuries were children and adolescents. Upper limb fractures were the commonest type of fractures (83.2%) seen among adolescents in Sri Lanka [ 15 ]. Since published data was not available in the local context to identify the risk factors and the burden of upper limb fractures among adolescents, the current study filled this gap in the body of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The study had revealed that 35.8% of patients with fractures following injuries were children and adolescents. Upper limb fractures were the commonest type of fractures (83.2%) seen among adolescents in Sri Lanka [ 15 ]. Since published data was not available in the local context to identify the risk factors and the burden of upper limb fractures among adolescents, the current study filled this gap in the body of knowledge.…”
Section: Introductionmentioning
confidence: 99%